Key Matrix Generation Using Random Functions in Hill Cipher Modulo 95 Cryptography - Bahtiar, Nurdin; Widodo, Aris Puji; Puspita, Nikken Prima (Integra: Journal of Integrated Mathematics and Computer Science, 2025)
In symmetric cryptography, the confidentiality of the chosen key and the security of its delivery mechanism are paramount to minimize the risk of unauthorized disclosure. Typically, in such systems, the sender and recipient focus primarily on the message (plaintext and ciphertext) rather than the complexities associated with key management. This approach aims to alleviate the burden of selecting a suitable and robust key for communicating parties. This study introduces a Hill Cipher modulo 95 cryptography method employing a matrix-based key, where key generation is achieved through a quantifiable randomization algorithm. The developed 2x2 key matrix facilitates a substantial number of possible keys, specifically 954 (exceeding 81 million). The key matrix generation process incorporates several functions, including those for ASCII character conversion, prime number verification, relative primality checks, modulo arithmetic, inverse modulo computation, determinant calculation, and inverse matrix determination. To simulate the encryption and decryption process, a desktop application was developed using the Lazarus Development IDE version 3.6. The application demonstrates effective generation of the required key matrix.